Environmental exposures and RNA N6-Methyladenosine modified long Non-Coding RNAs - Cayir, Akin (Critical reviews in toxicology, 2020)
Recent advances in the field of RNA modifications and long non-coding RNAs (lncRNAs) have provided substantial evidence on important biological functions. LncRNAs are defined as longer than 200 nucleotides which are not translated into proteins. The term "epitranscriptome" refers to all modifications in RNA types. Adenine-6 methylation (m 6 A) is the most common, dynamic and prominent modifications in coding and non-coding RNAs and has critical and previously unappreciated functional roles. Accumulation evidence indicated the association between RNA m6A modification and cancer and nonmalignant diseases. Recent studies reported that several lncRNAs including MALAT1, MEG3, XIST, GAS5, and KCNK15-AS1 are subject to m 6 A modification. It can be suggested that lncRNAs modified by m 6 A modification have substantive roles in diseases. Currently limited data are available regarding how environmental exposure affects m 6 A-modified lncRNAs. Furthermore, we do not know the interaction of environmental exposure and m 6 A-modified lncRNAs in development of adverse human health outcomes. Thus, in this systematic review, we aimed to present the data of the studies that reported a significant association between environmental exposure and expression/DNA methylation of m 6 A-modified long non-coding RNAs.